W. Horsley Gantt, Nick, and the Pavlovian Science at Phipps Clinic. (24th October 2016) - Ruiz, Gabriel; Sánchez, Natividad
Abstract: William Horsley Gantt is well known as one to the principal proponents of Pavlovian methodology in the U.S. After a long stay at Ivan Petrovich Pavlov's laboratory in Leningrad from 1925 to 1929, Gantt was invited by Adolf Meyer to join the Henry Phipps Psychiatric Clinic, where he founded and directed the Pavlovian Laboratory from 1930 to 1964. Soon after his arrival at Phipps Clinic in 1931, Gantt began a Pavlovian research program that included the investigation of nervous disturbances in dogs and clinical researches with psychiatric patients. In these studies, Gantt combined a physiological method (the conditional reflexes approach), with a psychiatric problem (nervous disorders) in the context of Meyer's psychobiology that established the person or individual as unit of analysis. This fact, concentrating upon a single individual, made Gantt studies with dogs recognizable and interesting to physicians, psychologists, and psychiatrists who also worked on individuals. In this paper, we use archival materials –including correspondence, notebooks, and unpublished autobiographical material- to present a case study, that of William Horsley Gantt and his dog Nick. We will explore the reasons why Gantt' studies on nervous disturbances with this dog captured the interest of psychiatrists and clinical psychologists.